2005
DOI: 10.1002/cne.20776
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression differences over a critical period of afferent-dependent neuron survival in the mouse auditory brainstem

Abstract: Deprivation of auditory nerve input in young mice results in dramatic neuron death in the anteroventral cochlear nucleus (CN), while the same manipulation performed in older mice does not result in significant neuronal loss. The molecular basis underlying this critical period of susceptibility to loss of afferent input remains largely unknown. One possibility is that developmental differences in baseline mRNA expression of specific genes could predispose CN neurons to either death or survival after deafferenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 58 publications
1
34
0
3
Order By: Relevance
“…A similar drop in differentially expressed genes during postnatal development could also be observed in microarray data obtained for the cochlear nucleus complex, another auditory brainstem structure. In this tissue, 6.2% of 22,690 oligos were differentially expressed between P7 and P14, and 0.13% were differentially expressed between P14 and P21, using criteria similar to ours (p Յ 0.05 and fc of Ն1.8) (32). Comparing all stages in the SOC, the largest number of differentially expressed oligos was observed between P0 and P25 (5,373 oligos, ϳ13.1%) ( Table 1).…”
Section: Resultssupporting
confidence: 64%
“…A similar drop in differentially expressed genes during postnatal development could also be observed in microarray data obtained for the cochlear nucleus complex, another auditory brainstem structure. In this tissue, 6.2% of 22,690 oligos were differentially expressed between P7 and P14, and 0.13% were differentially expressed between P14 and P21, using criteria similar to ours (p Յ 0.05 and fc of Ն1.8) (32). Comparing all stages in the SOC, the largest number of differentially expressed oligos was observed between P0 and P25 (5,373 oligos, ϳ13.1%) ( Table 1).…”
Section: Resultssupporting
confidence: 64%
“…This implies that bcl-2 may be inhibiting the upregulation of FasL expression that follows deafferentation of AVCN neurons that are beyond the critical period, ultimately preventing their death by suppressing the Fas/ FasL apoptotic pathway. Similarly, Harris et al (2005) found, using microarray analysis, that AVCN from mice within the critical period express higher levels of transcript for proapoptotic genes than AVCN from mice beyond the critical period and, conversely, AVCN from mice beyond the critical period express higher levels of transcript for prosurvival genes than AVCN from mice within the critical period. This indicates a developmental "switch" in AVCN from a complement of cellular mechanisms favoring induction of an apoptotic pathway to a complement of mechanisms that prevent or eliminate the apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…During maturation, the neurons undergo a transformation from being susceptible to deafferentation-induced death to being resistant to the same manipulation. The biological switch that transforms the way in which these neurons respond to removal of afferent input is yet to be characterized, although many likely cellular and molecular candidates have been suggested in both the auditory (Rubel et al, 2004;Harris et al, 2005) and visual (Taha and Stryker, 2005) systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, important differences exist between juvenile and adult brain plasticity with respect to speed, breadth, and type of changes inducible by internal or external stimuli (e.g. Harris et al, 2005;2008). At all developmental stages, neuroplasticity has many facets and includes the mutability on virtually all levels of neuronal organization, including volume growth, modifications of topographical maps, axon rerouting, dendritic outgrowth or retraction, cell death, mitosis, synaptogenesis, and molecular changes of various sorts.…”
Section: Auditory Brainstem Plasticitymentioning
confidence: 99%